2005
DOI: 10.1002/adsc.200404308
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Transfer Hydrogenation of Ketones and Imines with a Ruthenium N-Heterocyclic Carbene Complex

Abstract: Abstract:The dihydride ruthenium N-heterocyclic carbene complex Ru(IMes)(PPh 3 ) 2 CO(H) 2 (1) (IMes ¼ 1,3-dimesityl-1,3-dihydro-2H-imidazol-2-ylidene) is an efficient catalyst for both direct hydrogenation and transfer hydrogenation of ketones and imines, in the absence of base.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(37 citation statements)
references
References 29 publications
1
36
0
Order By: Relevance
“…A number of transition metal catalysts have been used for this transformation. The main focus has been on ruthenium(II) complexes [23][24][25][26][27][28][29]. However, in most of the cases, the reactions are effective only in the cases of ketones.…”
Section: Resultsmentioning
confidence: 99%
“…A number of transition metal catalysts have been used for this transformation. The main focus has been on ruthenium(II) complexes [23][24][25][26][27][28][29]. However, in most of the cases, the reactions are effective only in the cases of ketones.…”
Section: Resultsmentioning
confidence: 99%
“…Since the [Ru 3 (CO) 12 ]-catalyzed reaction was reported first by Jones' group,11 several ruthenium complexes have been tested for transfer hydrogenation of imines with 2-propanol. [12][13][14][15][16][17][18] Wang and Bäckvall reported that a Ru-PPh 3 complex, [RuCl 2 (PPh 3 ) 3 ], catalyzes transfer hydrogenation of imines with 2-propanol and that addition of K 2 CO 3 dramatically enhances the catalytic activity of the ruthenium complex. 12 The role of the base was ascribed to formation of an alkoxoruthenium species that undergoes further -H elimination to produce a cationic ruthenium hydride species.…”
Section: Resultsmentioning
confidence: 99%
“…use of hydrogen gas) and transfer hydrogenation of imines and ketones [33] . Isopropanol is used as the hydrogen source, with a catalyst loading of 2 mol%.…”
Section: Carbene -Based Catalystsmentioning
confidence: 99%